Rapid tumor growth with glial differentiation of central neurocytoma after stereotactic radiosurgery. (September 2016) - Tanaka, Hirotomo; Sasayama, Takashi; Yamashita, Haruo; Hara, Yoshie; Hayashi, Shigeto; Yamamoto, Yusuke; Fujita, Yuichi; Okino, Takeshi; Mizowaki, Takashi; Yamaguchi, Yoji; Tanaka, Kazuhiro; Kohmura, Eiji
Highlights: We describe a case of central neurocytoma (CN), which recurred after radiosurgery. An immunohistological comparison between the initial and recurrent CN was performed. The recurrent tumor had marked angiogenesis and intimal thickening of vessel walls. The recurrent tumor cells strongly expressed glial fibrillary acidic protein (GFAP), vascular endothelial growth factor (VEGF) and VEGF receptor. Abstract: Although stereotactic radiosurgery (SRS) is effective for central neurocytoma (CN), the long-term outcome of SRS remains unclear. We present a case of recurrent CN that was diagnosed 10 years after surgical resection and consecutive stereotactic radiotherapy. The patient was treated with SRS for the recurrent tumor, but underwent two-staged surgery once again due to rapid tumor growth. Histological features of the recurrent tumor were consistent with the diagnosis of CN. However, an increased Ki-67 proliferation index (3.4%), aberrant angiogenesis and glial differentiation of the tumor cells were observed, which were not identified in the initial CN. In addition, vascular endothelial growth factor (VEGF) and VEGF receptor were highly expressed in the recurrent tumor cells, as well as in the vascular endothelial cells. Our case suggests that malignant transition with aberrant angiogenesis and glial differentiation may be attributable to SRS.